Sosialisasi Dan Pelatihan Aplikasi FIGMA Untuk Siswa SMK YADIKA 5 Dalam Meningkatkan Keterampilan UI/UX - Gilang Herdiansyah; Alfarisi Gymnastiar; Ashapan Husnan; Satria Maulana; Tedi Harun (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
As an effort to improve students' abilities in user interface and user experience (UI/UX) design, a community service activity (PKM) with the theme "Socialization and Training of Figma Applications for SMK Yadika 5 Students in Improving UI/UX Skills" was carried out. Due to the fact that figama is a popular cloud-based design tool that is easy for students to use, figama was chosen as the main platform. This training was designed using a participatory learning approach. This method includes live demonstrations, independent practice, question and answer sessions, case studies, material presentations, and evaluations before and after the activity. The results of the activity showed that students better understood the basic concepts of UI/UX, were better at making wireframes, and were better at making interactive prototypes using Figma. Most participants stated that this training really helped them understand the importance of user-oriented digital design. This activity not only improved students' technical abilities, but also fostered their interest in the world of digital design and opened their eyes to careers in creative technology. It is hoped that this training will help students become competitive in digital skills in the era of industry 4.0. This is a real example of the Tri Dharma of Higher Education, especially in terms of community service in vocational education.